Pembrolizumab for advanced nonsmall cell lung cancer: Efficacy and safety in everyday clinical practice. (July 2019) - Ksienski, Doran; Wai, Elaine S.; Croteau, Nicole; Freeman, Ashley T.; Chan, Angela; Fiorino, Leathia; Brooks, Edward G.; Poonja, Zia; Fenton, David; Geller, Georgia; Irons, Sarah; Lesperance, Mary
Highlights: Poor ECOG PS patients are excluded from pembrolizumab advanced NSCLC trials. In this review, median OS was lower if ECOG PS 2 or 3 (versus ≤1) at baseline. Odds of high-grade adverse event was 6.3 fold higher if ECOG PS 2 or 3 (versus ≤1). Aside from pneumonitis, adverse events not associated with OS in studied cohort. Abstract: Objectives: While pembrolizumab improves overall survival (OS) in a subset of advanced nonsmall cell lung cancer (aNSCLC) patients (pts) in clinical trials, individuals with poor Eastern Cooperative Oncology Group performance status (ECOG PS) were excluded. Furthermore, some studies have identified a potential link between improved pt outcomes and development of immune related adverse events (irAE.) In a large provincial cohort, we studied the efficacy and safety of pembrolizumab for poor ECOG PS pts and whether irAE correlate with improved OS. Materials and methods: aNSCLC pts treated with pembrolizumab between 06/2015 and 08/2018 at BC Cancer were retrospectively identified. Kaplan-Meier curves of OS from initiation of pembrolizumab were plotted. 3-, 6-, and 9- month landmark Kaplan-Meier analysis was performed and log-rank tests used to determine an association of irAE subtypes with OS. Multivariable logistic regression identified variables associated with grade ≥3 irAE within 3 months of pembrolizumab initiation. Results: Of 190 pts, 74.2% were treatment naïve and 92.6% had PD-L1 expression ≥ 50%. Median OS in the 1st line and ≥2nd line settings were 24.3 months (95% CI, 9.7-not reached, NR) and 13.4 months (95% CI, 8.1-NR), respectively. Pts with ECOG PS 2/3 had lower median OS than if ECOG PS 0/1 (5.8 months vs. 16.7 months, p < 0.0001). In multivariable analysis, the odds of grade ≥ 3 irAE within 3 months was 6.3 fold higher if ECOG PS 2/3 versus 0/1 (p = 0.05). Development of pneumonitis at the 9 month landmark weakly correlated with decreased OS (p = 0.09). Conclusion: In the studied cohort, ECOG PS 2/3 pts had a significantly lower OS and greater odds of experiencing high-grade irAE than if ECOG PS 0/1. Development of irAE did not result in improved OS. Randomized trials to determine benefit of pembrolizumab for poor ECOG PS pts are needed.